Mega Tourism Marketing As A Modern Trend To Achieve Tourism Development In North African Countries - seffari, asma; chennam, naima (جامعة الوادي - University of Eloued, 2021)
Marketing Tourism is one of the most important modern trends adopted by countries to achieve tourism integration, especially those who have a potential to do so as North Africa countries. This paper aims to investigate the possibility of integration between the North African countries: Algeria, Morocco, Tunisia and Egypt, for marketing the mega tourism destination, given their geographical proximity and similar culture. The results showed that it was not difficult to achieve integration among countries under study; this can be achieved through the joint efforts of governments, companies and individuals to develop a unified marketing policy that enables them to compete in the global tourism market and thus increase their share
مقال
Keywords: Integrated Tourism Marketing; Tourism Development; Mega Tourism Destination; North African Countries.